2005
DOI: 10.1086/431893
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Relationship between Twist in Active Region Magnetic Fields and Solar Flares

Abstract: Twisted magnetic field lines in solar active regions constitute stressed flux systems, the reconnection of which can release the stored (excess) magnetic energy in the form of solar flares. Using co-registered photospheric vector magnetograms and chromospheric H images for 29 flares, we explore the spatial relationship between these flares and the magnetic topology of the active regions in which they occur. We find two dominant trends. First, flares are preferentially initiated in subregions that have a high g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Even though the dips are plotted to 1 PSH this does not mean that material sitting in these dips will in fact be visible in Hα. An additional requirement for it to be visible is that the column mass along the line of sight be sufficiently high (≈1 × 10 −5 g cm −2 , Gouttebroze, Heinzel, and Vial, 1993;Heinzel and Anzer, 2006). Therefore after computing the dips a simple hydrostatic atmosphere model is applied to determine the column mass from different viewing angles.…”
Section: The Modelsmentioning
confidence: 99%
“…Even though the dips are plotted to 1 PSH this does not mean that material sitting in these dips will in fact be visible in Hα. An additional requirement for it to be visible is that the column mass along the line of sight be sufficiently high (≈1 × 10 −5 g cm −2 , Gouttebroze, Heinzel, and Vial, 1993;Heinzel and Anzer, 2006). Therefore after computing the dips a simple hydrostatic atmosphere model is applied to determine the column mass from different viewing angles.…”
Section: The Modelsmentioning
confidence: 99%
“…From a sample of 17 vector magnetograms, Falconer et al (2003) found that the length of the strong-field and strong-gradient main neutral line (Lsg) is a viable proxy for the overall non-potentiality of active regions that can be measured from longitudinal magnetograms. Hahn et al (2005) studied co-registered photospheric vector magnetograms and chromospheric Hα images for 29 flares and found that flares tend to originate in regions of a high twist gradient and lie close to chirality inversion lines.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter is also used as a measure of twist in observational studies (see Liu et al 2014or Hahn et al 2005. It should be noted that this is not the α we vary in Group 2 and we have denoted this as α L to differentiate between the two.…”
Section: Twistmentioning
confidence: 99%